THE EFFECT OF EXHAUST EMISSIONS L, O2, CO, CO2 AND HYDROCARBON FOR PERFORMANCE OF ALL NEW ERTIGA AUTOMOTIVE - Batutah, Moh Arif; Nguyen, Duong Tuan Anh (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2025)
The automotive with various and brands, both from Asia and Europe are all here. How much exhaust emissions are produced if each person uses the motor vehicle itself. The purpose of this study is to compare the quality of fuel used with the exhaust emissions of l, O2, CO, CO2 and HC produced. The test method is conducting sampling tests on All New Ertiga and testing emissions using a Gas Analyzer Tester. The fuel variants used in the emission testing process are pertamax, pertamax + octan booster, pertamax turbo and pertamax turbo + octan booster. With several variants of fuel used, can find effect l, O2, CO, CO2 and HC produced on these automotive. The best engine performance at 115 Nm of torque with emissions are still below TLV (threshold limit value) for pertamax, while for pertamax turbo the best performance at 120 Nm with emissions below TLV.